Evaluation of the Teaching Factory Program Using the CIPP Evaluation Model (Context, Input, Process, Product) - Iqbal, Muhamad; Arthur, Riyan; Saleh, Rosmawita (Universitas Pendidikan Indonesia (UPI), 2025)
The high demand for labor in the industrial sector and the open unemployment rate in Indonesia, which reaches 5.32% of the total workforce, indicate that the quality of Indonesian Human Resources is still relatively low and requires serious attention. To address these issues, the Directorate of Vocational School Development encourages the implementation of the teaching factory program as an innovative strategy to enhance students' competencies to better align with the dynamic and competitive demands of the industrial world. This research aims to evaluate the implementation of the teaching factory program in the competencies of Interior Design and Furniture Engineering at Vocational School 52 Jakarta using the CIPP evaluation model (Context, Input, Process, Product). This research uses a mixed-methods approach with an evaluative method. Data collection was carried out using questionnaire instruments, in-depth interviews, direct field observations, and relevant documentation studies. All the data obtained were analyzed descriptively and narratively to gain a comprehensive and in-depth understanding of the program's implementation. The evaluation results show that in all aspects of the evaluation, most indicators have met the established criteria. However, several improvements are still needed, such as involving education experts in the preparation of curriculum documents, refining learning documents like MoUs and jobsheets, and enhancing job placement and continuous development for graduates. This recommendation is expected to serve as a basis for policy-making to optimize the implementation of the teaching factory so that it can produce graduates who are truly job-ready and adaptable to changes in the industrial world.